Nilai Moral Film Animasi Buddhis Pada Laman Facebook Daai Tv Indonesia: Sebuah Analisis Semiotika - Renia Astria Linsih; Kadek Yudi Murdana; Milia Panna Santi (Jounal Nyanadassana, 2023)
Abstract: Movies are mass communication tool that utilizes depictions of societies’s real-life scenarios as a means to convey specific messages or information. One kind of films is animation that replete with symbols, emblems, and profound meanings. Animations showcased on the Facebook platform by DAAI TV INDONESIA portray captivating Buddhist tales which is rich in moral values. The aim of this research is to identify the implied moral values within three animated films by DAAI TV INDONESIA. The research method used in this research is qualitative descriptive, utilizing a semiotic analysis approach based on Roland Barthes' five semiotic codes: the Hermeneutic Code, the Semic Code, the Symbolic Code, the Proaretic Code, and the Cultural Code. The primary data for this research consists of three animated film titles: Rahula, The Hunter's Trap, and Mahakassapa's Watermelon. Meanwhile, secondary data were gathered from various sources such as books, journals, theses, and online media. The research findings confirm that semiotic analysis effectively reveals a variety of moral values within animated films. Rahula embodies values such as skill, humility, wisdom, joy in giving advice, willingness to assist, and bravery. The Hunter's Trap conveys moral messages about responsibility, wisdom, compassion, kindness, and hard work. Meanwhile, Mahakassapa's Watermelon highlights honesty, patience, generosity, wisdom, and respect. Among these three Buddhist animated films, wisdom emerges as the most prominently dominant moral value.